Decoding the Duterte Doctrine: Understanding Strategic Changes in Philippine Foreign Policy during Duterte Administration - Gerale, Christopher Paller (Global Focus, 2024)
This article employs a sophisticated neoclassical realist framework to conduct a comprehensive analysis of the intricate landscape of Philippine foreign policy under the administration of former Philippine President Rodrigo Roa Duterte, elucidating the contours of the so-called “The Duterte Doctrine”. This encompasses a nuanced exploration of the nation's role as a middle power, focusing on the pillars of national security, economic diplomacy, and the safeguarding of overseas Filipinos. Employing an analytical lens that intricately weaves systemic pressures and domestic imperatives, the study meticulously unravels the historical trajectory of Philippines-USA relations and the evolving dynamics in the Philippines-China relationship. Methodologically, a discerning review of historical events, policy decisions, and diplomatic maneuvers is undertaken to unveil discernible patterns and strategic recalibrations within the nation's foreign policy landscape. The main findings underscore a diplomatic chess game in the Philippines-China relationship, marked by a strategic departure in defense posture with the cessation of joint military exercises with the U.S. Economic diplomacy, encapsulated in the Duterte Doctrine, manifests as a fervent pursuit of diversified economic partnerships, concurrently raising cogent concerns about potential economic dependence. The analysis accentuates the adaptive resilience of Philippine foreign policy in response to the evolving global landscape, thereby substantively contributing to regional stability. As a middle power, the Philippines astutely leverages its agency amid great power competition while assiduously upholding principles of international law and justice, necessitating nuanced and context-specific approaches to maintain a delicate balance between traditional alliances and emerging economic partnerships.Keywords: China, Duterte Doctrine, Philippines, Rodrigo Roa Duterte